Geography on an ontological-existential basis through Heidegger’s phenomenology-hermeneutics: the meaning of existential being-in - Tosta dos Reis, Luis Carlos; Santos, Josimar Monteiro; Silva, Akylla Coser Chiabai (Geografares, 2021)
The article considers the relation between Geography and Heidegger’s thought, focusing on the problem of ontological solid ground of this science. Its goal is to promote rehabilitation of investigation concerning the ontology in Geography through a specific way in which the philosopher apprehends the phenomenological method. For this, the discussion will be oriented for the exposition of the existential being-in which make viable the phenomenological interpretation of space as originary phenomenon that, for Heidegger, corresponds to the existential space that is at the base of all conceptual representation of sciences that lead their researches through a specific theoretical determination about space, such as Geography. To do so, it is essential to make ontological research in Geography compatible with the analysis of human being-there contained in Being and Time. The article is justified insofar as it constitutes a path that is little developed in the discipline, which usually subjects the subject to a strictly theoretical treatment.